Desenvolvimento de filmes poliméricos com MgB4O7:Ce,Li para aplicações dosimétricas - Santos, Caroline Castro dos Santos (2018)
Dosimeters used in practices that involve ionizing radiation are essential, mainly in diagnostic radiology and radiotherapy. Radiation dosimetry allows the quality control, recording and assessment of the entrance exposure inside the body during a treatment. However, none of the currently available dosimeters enables accurate dose measurements in large areas or irregular surfaces of the human body. Thus, in order to improve dosimetric tools, it is being investigated the development of flexible and impermeable dosimetric films, formed by a polymer matrix of polyvinyl chloride (PVC), with microcrystals of MgB4O7:Ce,Li, produced by solid state synthesis and optically stimulated luminescence (OSL) emitters. The crystals with different characteristics were inserted in plastic matrices to verify their dosimetric behavior. Some of the possible solvents for the production of the films were evaluated, observing their effects on the crystals in OSL emission. The structural properties were analyzed by x-ray diffraction, before and after the chemical action of each solvent. The sensitivity of the film to radiation dose have been verified. In this way, the results showed that acetone-benzene solution is the most favorable for the production of films because it does not cause large changes in the structure and luminescent properties of the crystals. In addition, the results have shown that these films can contribute significantly to the production of new 2D dosimeters favorable to dose measurements near the skin surface.